Application Of Fuzzy Delphi Method (Fdm) To Reach The Experts Consensus On The Construction Osh Modifying Risk Factor - Mokhtar Zamimi Ranjan, Mohd Rafee Baharudin, B.T. Hang Tuah Baharudin, Muhammad Razif Mahadi (International Journal of Advanced Science and Technology, 2020)
Occupational Safety and Health (OSH) is an intricate phenomenon in construction. The aim of this study was to achieve an agreement from experts on the appropriateness of the questionnaire elements and their items for the evaluation of the construction OSH modifying risk factor. A compilation of questionnaires pertaining to the construction OSH modifying risk factor was collected based on a literature search.  A most essential step in forming a census questionnaire set is to determine the suitable elements and their items. The retention of insignificant elements and their items and the removal of key elements and their items would distort the course of the particular study. The Fuzzy Delphi Method (FDM) is used to consolidate a consensus within a panel of experts on the acceptability of each element and their items. Panellist comprises of 15 OSH experts from the numerous organizations. The process of validation is based on the principles of Triangular Fuzzy Numbers and Defuzzification. Post FDM analysis indicated the first pre-requisite (threshold value (d) ≤ 0.2) and the second pre-requisite (expert agreement higher than 75%) were met, so all elements and their items were approved. The content of the instrument appears to be legitimate and is therefore now prepared for a further process that will contribute to the investigation of OSH modifying risk factor factors in the Malaysian construction industry.